Gloc-9 as organic public intellectual hip and polished, raw and cool - Mendoza, Lara Katrina T. (Plaridel, 2017)
Access online through this link: https://www.plarideljournal.org/article/gloc-9-organic-public-intellectual-hip-polished-raw-cool/#google_vignette